ITEM RESPONSE THEORY AS A TOOL FOR THE ESTIMATION OF A LANGUAGE TEST - M. V. Makarych (Системный анализ и прикладная информатика, 2018)
Being a part of applied linguistics a language test plays an important role in a modern society. It is used for evaluating person’s language skills not only at educational establishments but also while acquiring citizenship or getting a job. The purpose of the article is the development of a special technique for language test estimation using Item Response Theory (IRT). Short historical review of methods for learning ability estimation is represented. Fundamental principles of Classical and Modern Test Theory is described. The author considers a linguodidactical test as a classical test that patterns four main principles by Kockota V. A. The methodology for the evaluation process of English linguodidactical test with the help of IRT is described in details. Such a linguodidactical test will take into account the level of tasks difficulty, the total amount of tasks, the level of person’s knowledge and testing conditions. This methodology helps to create a test that can assess the real grade of a person being tested.